Advanced techniques in minimally invasive and robotic colorectal surgery (New York : Springer, 2015)
Laparoscopic colectomy has been introduced in the early 90ies as a new technique with proven improvement in short and long term outcome. Despite significant patient benefits the overall adoption rate remains low. On the other hand significant more advanced techniques such as single incision laparoscopy, robotics and transanal access surgery have been introduced in the last several years and are rapidly evolving. Therefore a significant gap between the practicing community surgeon and innovator seems to exist. Advanced Techniques in Minimally Invasive and Robotic Colorectal Surgery bridges that gap and provides a foundation summarizing and organizing all classic and new techniques in minimally invasive colorectal surgery available in literature and from masters within the field.It provides tips and tricks that allow the user to move up the learning curve, manage difficult scenarios, overcome challenges, increase the utilization of minimal invasive techniques and decrease the conversionto open surgery. By enhancing the surgical tool box the surgeon will be able to progress from the novice to the master. Rather than describing operative procedures which may be very biased by an individual author, the guide provides alternative building blocks of various difficulty for different procedures which can be then tailored to the patient and surgeon`s own comfort level and experience. Advanced Techniques in Minimally Invasive and Robotic Colorectal Surgery will serve as a inspirational guide for the innovator of the future. It will allow surgeons of all levels to better adapt to inevitable changes in future techniques and will be of great value to general surgeons, colon and rectal surgeons, minimally invasive surgeons as well as residents and fellows.
La función de los autores fue determinada por el catalogador
También disponible en formato Epub